Identifying supply chain actors’ barriers to implementing synchromodality through an operational perspective - Mylena Cristine Rodrigues de Jesus; Edwin van Hassel; Thierry Vanelslander (Transportation Engineering, 2025)
Despite the spare capacity of inland waterways, roadway transport remains the predominant mode of freight movement. It has been facing several issues, including bottlenecks and environmental concerns. While both multimodality and synchromodality aim to combine different modes of transport for greater efficiency and sustainability, synchromodality uniquely considers real-time information to select the most efficient and cost-effective transport modes. It presents a promising solution for optimising freight transport systems but faces significant implementation challenges, particularly in fostering collaboration among multiple actors and ensuring coordinated planning and operations. This study examines the main factors hindering mode shift. It evaluates the level of collaboration among supply chain actors in implementing a more flexible and collaborative freight transport system, mainly focusing on inland waterways. The methodology of this paper involves a literature review, survey development, data collection, and data analysis; 68 supply chain stakeholder perspectives are explored, and the challenges and opportunities of synchromodal transport are explored. The findings reveal the importance of cost, service quality, distance and infrastructure availability in mode choice processes. The perception of supply chain actors on the level of integration among transport modes and collaboration across stakeholders was also targeted, highlighting critical barriers to the implementation of synchromodality. The research underscores the need for targeted policy interventions, such as promoting stakeholder collaboration, enhancing traffic management systems, and clarifying to the stakeholders the benefits of the shift toward more efficient and sustainable freight transport solutions.